Characterizing the Eemian-Weichselian transition in northwestern Europe with three multiproxy speleothem archives from the Belgian Han-sur-Lesse and Remouchamps cave systems. (15th March 2019) - Vansteenberge, Stef; Verheyden, Sophie; Genty, Dominique; Blamart, Dominique; Goderis, Steven; Van Malderen, Stijn J.M.; Vanhaecke, Frank; Hodel, Florent; Gillikin, David; Ek, Camille; Quinif, Yves; Cheng, Hai; et al.
Abstract: Interglacial to glacial transitions represent the most drastic turnovers in the Quaternary climate system. Yet, millennial-scaled climate variability and stochastic internal variability that result in (inter)glacial transitions remain poorly understood. Here, three speleothems from two different cave systems in Belgium are investigated to characterize the Eemian to early Weichselian transition. The speleothems show high reproducibility for δ 13 C, interpreted as a proxy for past vegetation activity, controlled by type of vegetation above the cave. All three speleothems show a drastic increase in δ 13 C between 118 and 117 ka, reflecting a rapid change in vegetation from last interglacial temperate tree species towards glacial open-grass vegetation. This transition shows a strong affinity with the Late Eemian Aridity Pulse (LEAP) at 118 ± 1 ka, previously identified in pollen records from Western Germany. An age of 117.7 ± 0.5 ka is determined for the start of this transition in the Belgian speleothems. The speleothem records show a distinct transition in the proxies between Eemian optimum conditions and increased variability during the glacial inception and therefore the Eemian-Weichselian transition is set at 117.7 ± 0.5 ka in the speleothem records. High-resolution trace element analysis shows that the transition is initiated by a cooling pulse followed by a decrease in precipitation. Through comparison with other archives, including North-Atlantic sedimentary records, it is proposed that the transition at 117.7 ka constitutes an internal climate response caused by a substantial input of freshwater from degraded ice-sheets by the end of the Eemian (∼120-118 ka). Highlights: A paleoclimate reconstruction of the Eemian-Weichselian transition is presented. The EWT occurs at 117.7 ± 0.5 ka in the records. This transition is linked with a larger regional cooling. There is evidence for a climatic connection with the North Atlantic region.